Effect of Variable Pressure-assisted Immersion Process Using (−)-epicatechin on the Color, Flavor, and Polycyclic Aromatic Hydrocarbons Content in Roasted Beef Meat - Hui, Teng; Fang, Zhengfeng; Hamid, Nazimah; Ma, Qianli; Cai, Kezhou (Elsevier BV, 2023)
Polycyclic aromatic hydrocarbons (PAHs) are more easily formed in beef meat than other meats. A previous study confirmed the inhibitory effect of (−)-epicatechin on PAHs in a fat model system. However, (−)-epicatechin solution demonstrates colloidal properties at high concentrations. Hence a variable pressure immersion method was applied to infuse (−)-epicatechin in beef cubes. The fixed variable pressure-assisted immersion process using (−)-epicatechin that ranged from 0.2 mM/L to 5.0 mM/L was found to influence color, flavor, and PAHs dose-dependently. The 0.2 mM/L (−)-epicatechin treatment stabilized color properties, reduced PAHs content, and promoted the formation of volatiles and free amino acids. However, the use of more than 1.0 mM/L (−)-epicatechin, gradually decreased the values of brightness (L*) and yellow to blue color (b*), volatiles and free amino acids content, and reduced the inhibitory effect on PAHs. Therefore, the variable pressure-assisted immersion process of meat in 0.2 mM/L (−)-epicatechin can inhibit PAHs formation without compromising flavor properties of roasted beef.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3003 Animal Production; 0702 Animal Production; 0904 Chemical Engineering; 0908 Food Sciences; 3006 Food sciences; 3210 Nutrition and dietetics; 4004 Chemical engineering